Did the plan Sénégal emergent affect cropping decisions in the Senegal River Basin? - Charles B. Moss; Samba Mbaye; Anwar Naseem; James F. Oehmke (Economies, 2018)
One of the basic debates in African development is whether agriculture can be the instrument for the transformation of a rural economy. A common question is whether agricultural policies can provide the impetus to move agriculture in developing economies from subsistence to commercial agriculture. Senegal's Plan Sénégal Emergent (PSE) provides a data point in this discussion. Senegal and international donors invested in agricultural supply chains starting in 2012 to facilitate the emergence of commercial agriculture for peanuts, rice, and vegetables. This study focuses on these investments in the Senegal River Valley of northern Senegal. The empirical results presented in this study provide evidence that farms in the Senegal River Valley impacted by PSE have moved away from subsistence agriculture by planting more hectares in commercial crops.
Keywords: O12; O13; Q12; Q18; 330; Senegal; agricultural and rural transformation; information approach